Pengaruh Penggunaan Tiktok sebagai Sumber Informasi terhadap Literasi Digital Siswa - Asri Neli Putri; Suparmi Suparmi; Henri Yanto Daulay; Vicky Rohmatia (SAP (Susunan Artikel Pendidikan), 2025)
This study aims to determine the influence of the use of TikTok as a source of information on students' digital literacy at SMK Muhammadiyah 1 Pekanbaru. This research is based on the high intensity of TikTok use among students. This type of research is quantitative with a simple linear regression approach. The research sample amounted to 67 students who were selected using the Slovin formula. Data were collected through observation, documentation, and questionnaires, then analyzed using validity, reliability, normality, homogeneity, and simple linear regression tests. The results of the study show that the use of TikTok has a positive and significant effect on students' digital literacy. Regression analysis showed an R value of 0.449 with an R Square of 0.201, which means that 20.1% of digital literacy variations can be explained by TikTok use, while 79.9%. The conclusion of this study is that the use of TikTok can contribute to improving students' digital literacy. Therefore, it is recommended that schools and teachers can direct their students to utilize social media, especially TikTok, not only as a means of entertainment, but also as a learning medium and the improvement of critical, wise, and productive digital literacy skills